Strategi Pengemasan Informasi Pada Satuan Humas : Sosialisasi di Divisi Humas Polri - Prisgunanto, Ilham (Jurnal Pengabdian Kepada Masyarakat Kalam, 2023)
Strategies and tactics in communication are necessary in efforts to achieve the implementation of existing public relations programs. Many people don't understand what strategy and tactics are in communication. The community service carried out by STIK PTIK is an effort to provide an explanation of the meaning of strategy and tactics in communication, especially in packaging information. This is in line with the world having entered the virtual digital era which utilizes all the information available in information networks in existing network channels. The community service method used is by using direction and outreach to all public relations levels in the Indonesian National Police Public Relations Division and even at the Regional Police level in the Public Relations Sectors in Polda-Polda throughout Indonesia which was held on 29-31 August 2023. From socialization and briefing There are many members of the National Police in the public relations sector who do not understand that there are strict strategies and tactics in packaging information on internet networks. Likewise with processing and monitoring hoax analysis using the Communicator, Communicator, message and channel models as well as feedback in the SIP (Social Information Processing) study. It is necessary to develop strategies and tactics that exist in academic and scientific studies in Polri public relations practices in the field.